Investigation of the Law of Natural Gas Phase Behavior during the Migration and Reservoir Formation - Longlong Li; Jiaren Ye; Minqi Li; Lin Pan (Geofluids)
It is of great significance to understand the phase regime of natural gas migration under high temperature and high pressure in the DF1-1 structure of Yinggehai Basin, South China Sea, to predict natural gas accumulation and evaluate resource reserves. However, the existing methane solubility models are not suitable for the higher temperature and pressure range required under current geological conditions. Through a self-designed experimental equipment with high precision, the solubility of CH4 in deionized water can be measured in a wide range of temperatures (313.15-473.15 K) and pressures (5-200 MPa), and a reliable pressure-temperature-solubility segmented model is obtained by fitting. Using this model, we found that if the free-phase natural gas accumulated in the DF1-1 structural reservoir is completely dissolved in the water-soluble phase, the required formation water volume is much higher than the actual calculated formation water storage. Therefore, it can be inferred that the natural gas generated from the source rock of the DF13-1 structure mainly migrated and accumulated in the form of the free phase.